NILAI TAMBAH PENGOLAHAN IKAN TERI DI DESA KALIBURU KECAMATAN SINDUE TOMBUSABORA DI KABUPATEN DONGGALA SULAWESI TENGAH - Ahsan Mardjudo; Asrawati Asrawati; Samsudin Samsudin; ningsih ningsih (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2022)
The purpose of the Mitra Desa Development Program (PPDM) is to increase the knowledge and skills of women fishermen groups through the transformation of anchovy processing technology that provides added value and economic value, creates jobs through the development of home industry business management and increases community income through sales of fish processing products. anchovy in the form of anchovy sauce, anchovy pancakes and anchovy burger. In this PPDM activity, the methods developed are educational and training activities, as well as demonstrations of making various products derived from anchovy raw materials. In addition, it uses a learning by doing approach through the home industry group, namely learning while working / trying. Through this PPDM, it will develop a home industry based on the potential of anchovy resources. The application of PPDM to partner groups is expected to be able to develop the potential of anchovy resources to increase other products of economic value. Development of knowledge, skills and mastery of technology, especially Appropriate Technology (TTG) for coastal communities, especially for women who are able to access the potential that exists in their environment, so that they can increase family income towards a prosperous and independent society. The realization of PPDM is the implementation of training on anchovy processing which produces anchovy chili sauce, anchovy pancakes and anchovy burgers